Nomenclatural notes on Pothos roxburghii and related names (Araceae) - Deng, Yun-Fei (Phytotaxa, 2017)
Pothos Linnaeus (1753: 968) is a palaeotropic genus of approximate 70 species in the family Araceae and distributed in tropical and subtropical regions from Madagascar to Asia and Western Oceania (Boyce 2000, 2009, Hay 1995, Boyce & Hay 1998, 2001, Mabberley 2017).